Possessive Construction in Russian and Indonesian Noun Phrases: Contrastive Analysis and Translation - Tri Yulianty Karyaningsih (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
This paper aims to discuss the comparison between possessive constructions in Russian and Indonesian noun phrases. Since both of the languages have different grammatical systems, their possessive constructions may also be different. The differences are discussed using a contrastive analysis approach. However, the similarities between them are also taken into consideration following one of the practical purposes of contrastive analysis, namely, to aid the translation process. The theory employed in this research is eclectic. The research method employed in this research is descriptive method with contrastive analysis model. In addition, for translation analysis, word-for-word and literal methods are used here. The data in this research are collected from the Russian National Corpus and some selected literary works in Russian and Indonesian. The result suggests that there are some structural differences and similarities between Russian and Indonesian in terms of word order, attributive categories, and grammatical categories of the elements constituting noun phrases. The results of this comparison can be referred to in the translation of possessive construction of both languages so that the closest equivalent is found following the rules of each language.